Digital Branding Strategy Of Islamic Boarding School Students In Increasing The Attraction Of Prospective Students A Systematic Review Of The Literature - Hafidatun Nabila; Yusril Ihza Saputra; Uryatul Hikmah; Aminullah Aminullah; Moh. Holidi; Febi Febrianto; Umar Manshur (Universitas Nurul Jadid, 2025)
This study analyzes the digital branding strategies of Islamic boarding schools (pesantren) to increase the attractiveness of prospective students through a literature review approach. The era of the Industrial Revolution 4.0 and the development of digital technology have encouraged Islamic boarding schools to adapt by utilizing digital media such as websites, social media, and digital da'wah content as strategic tools to build a positive image, expand the reach of information, and increase public trust. This strategy encompasses not only the visual aspects and identity of the institution, but also the display of religious values, culture, the character of the kiai (Islamic scholars), and innovation in content presentation. Social media such as Instagram, YouTube, TikTok, and Facebook have become primary platforms for effective two-way communication, supporting the branding process, and building emotional relationships with the community. However, the implementation of digital branding in Islamic boarding schools faces challenges such as limited human resources, digital literacy, and professional content management. This study emphasizes the importance of integrating Islamic values with technological innovation to maintain the relevance of Islamic boarding schools in the digital era and strengthen the institution's competitiveness and reputation. It is hoped that the results of this study will provide a systematic and comprehensive overview of Islamic boarding school digital branding practices as an important strategy in attracting prospective students and building a positive image in the eyes of the community.